Genius talk : conversations with Nobel scientists and other luminaries / Denis Brian. - Brian, Denis. (Plenum Press, 1995)
This unique work draws on the greatest minds of our time - Linus Pauling, Richard Feynman, Hans Bethe, George Wald, Paul Dirac, Arno Penzias, Ashley Montagu, Theodor Reik, Hans Selye, and Roger Sperry, among many others - in the pursuit of discovering their distinct views on life, the mind, and the cosmos. Denis Brian, the celebrated biographer of Ernest Hemingway, interviewed this stellar cast of Nobel Prize winners and other luminaries in science, psychology, and neuroscience, asking them about their lives, their accomplishments, and their hopes for science in the future. He, moreover, gives them the opportunity to apply their keen imaginations and treasure trove of insights to matters outside the boundaries of the purely scientific - their beliefs in God, the supernatural, and even the possibility of life elsewhere - with truly stunning results.